Molecular Organization of Sarcoglycan Complex in Mouse Myotubes in Culture - Chan, Yiu-mo (The Rockefeller University Press, 1998)
The sarcoglycans are a complex of four transmembrane proteins (α, β, γ, and δ) which are primarily expressed in skeletal muscle and are closely associated with dystrophin and the dystroglycans in the muscle membrane. Mutations in the sarcoglycans are responsible for four autosomal recessive forms of muscular dystrophy. The function and the organization of the sarcoglycan complex are unknown. We have used coimmunoprecipitation and in vivo cross-linking techniques to analyze the sarcoglycan complex in cultured mouse myotubes. We demonstrate that the interaction between β- and δ-sarcoglycan is resistant to high concentrations of SDS and α-sarcoglycan is less tightly associated with other members of the complex. Cross-linking experiments show that β-, γ-, and δ-sarcoglycan are in close proximity to one another and that δ-sarcoglycan can be cross-linked to the dystroglycan complex. In addition, three of the sarcoglycans (β, γ, and δ) are shown to form intramolecular disulfide bonds. These studies further our knowledge of the structure of the sarcoglycan complex. Our proposed model of their interactions helps to explain some of the emerging data on the consequences of mutations in the individual sarcoglycans, their effect on the complex, and potentially the clinical course of muscular dystrophies.